Numerical simulation of extrusion of FeMnSiCrNi/NiTiNb dissimilar shape memory alloy composite tube based on finite element method and cellular automaton. Issue 1 (1st December 2022) - Jiang, S Y; Sun, D
Abstract : FeMnSiCrNi/NiTiNb dissimilar shape memory alloy composite tube is firstly put forward and it can be fabricated by means of isothermal extrusion. Based on Arrhenius constitutive model of FeMnSiCrNi and NiTiNb shape memory alloys, isothermal extrusion of FeMnSiCrNi/NiTiNb dissimilar shape memory alloy composite tube is simulated by rigid viscoplastic finite element method. It can be found that the deformation zone of the dissimilar shape memory alloy composite tube is always in a three-dimensional compressive stress state during extrusion, and the deformation of the inner tube is obviously higher than that of the outer tube. It is necessary to guarantee the interface compatibility between the inner tube and the outer tube during isothermal extrusion of FeMnSiCrNi/NiTiNb dissimilar shape memory alloy composite tube. The relationship between macroscopic process variables and microscopic variables during plastic deformation of FeMnSiCrNi shape memory alloy tube at high temperature is established by coupling finite element simulation and cellular automaton simulation. The microstructural evolution of FeMnSiCrNi shape memory alloy in different deformation zones during isothermal extrusion of dissimilar shape memory alloy composite tube is simulated. It can be concluded that the grain size of dynamic recrystallization is reduced with the increase of plastic strain in the deformation zone.